2020
DOI: 10.1073/pnas.1912074117
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-directed glycosylation of chromatin factors represses retrotransposon promoters

Abstract: The mechanisms by which methylated mammalian promoters are transcriptionally silenced even in the presence of all of the factors required for their expression have long been a major unresolved issue in the field of epigenetics. Repression requires the assembly of a methylation-dependent silencing complex that contains the TRIM28 protein (also known as KAP1 and TIF1β), a scaffolding protein without intrinsic repressive or DNA-binding properties. The identity of the key effector within this complex that represse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 53 publications
1
47
0
Order By: Relevance
“…Recently, a study identified another novel interaction partner of Trim28. The O-linked beta-N-acetylglucosamine transferase (OGT) and Trim28 have been shown to co-localize at methylated promoter regions of ERVs [73]. O-linked glycosylation is a newly described chromatin mark, which is suggested to play a crucial role in transcriptional silencing of ERVs [73].…”
Section: Trim28 As a Master Regulator Of Erv Silencingmentioning
confidence: 99%
“…Recently, a study identified another novel interaction partner of Trim28. The O-linked beta-N-acetylglucosamine transferase (OGT) and Trim28 have been shown to co-localize at methylated promoter regions of ERVs [73]. O-linked glycosylation is a newly described chromatin mark, which is suggested to play a crucial role in transcriptional silencing of ERVs [73].…”
Section: Trim28 As a Master Regulator Of Erv Silencingmentioning
confidence: 99%
“…[34][35][36] However, many other chromatin modifications, such as O-GlcNAc, 5hmC or H3K4me3, are also enriched on subsets of TE, suggesting that the epigenetic regulation of mobile elements may be more complex than previously anticipated and warrants further investigation. [37][38][39][40] Notably, a significant proportion of mammalian noncoding sites enriched for chromatin modifications do not coincide with either enhancers or TE. Epigenetic aberrations at these unannotated regions have already been linked to human syndromes, [41] implying that the functional interrogation of chromatin marks at non-genic regions will be instrumental to understand the mechanisms that govern genome regulation in both physiological and pathological circumstances.…”
Section: What Is the Function Of Epigenetic Marks At Non-coding Loci?mentioning
confidence: 99%
“…In addition to its effects on the process of DNA demethylation, OGT has been found to be involved in gene silencing mediated by DNA methylation. OGT selectively associates with the scaffolding protein TRIM28 only in the presence of methylated DNA (Boulard et al, 2020). It has been proposed that O-GlcNAcylation of chromatin modifiers that interact with TRIM28 is required at the sites of retrotransposon promoters to repress their transcription (Boulard et al, 2020).…”
Section: Ogt and Dna Methylationmentioning
confidence: 99%
“…OGT selectively associates with the scaffolding protein TRIM28 only in the presence of methylated DNA (Boulard et al, 2020). It has been proposed that O-GlcNAcylation of chromatin modifiers that interact with TRIM28 is required at the sites of retrotransposon promoters to repress their transcription (Boulard et al, 2020). This suggests disruption of O-GlcNAc cycling may lead to increased genome instability in addition to the contribution of impaired DNA damage response described above.…”
Section: Ogt and Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation